2020
DOI: 10.1177/2050312120918268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nottingham Hip Fracture Score, Age-Adjusted Charlson Comorbidity Index and the Physiological and Operative Severity Score for the enumeration of Mortality and morbidity as predictors of mortality in elderly neck of femur fracture patients

Abstract: Background: This study evaluated the use of several risk prediction models in estimating short- and long-term mortality following hip fracture in an Australian population. Methods: Data from 195 patients were retrospectively analysed and applied to three models of interest: the Nottingham Hip Fracture Score, the Age-Adjusted Charlson Comorbidity Index and the Physiological and Operative Severity Score for enUmeration of Mortality and Morbidity. The performance of these models was assessed with receiver operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The association between the CCI and postoperative mortality has been observed in numerous studies [ 7 , 8 , 9 , 38 , 43 , 44 ]. The ability of the CCI to predict postoperative mortality in hip fracture patients has also been compared to the NHFS and POSSUM in prior studies [ 45 , 46 ]. In some, the NHFS performs slightly better and in others POSSUM performs marginally worse, but overall, these indices have a comparable predictive ability when all studies are taken into consideration [ 45 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between the CCI and postoperative mortality has been observed in numerous studies [ 7 , 8 , 9 , 38 , 43 , 44 ]. The ability of the CCI to predict postoperative mortality in hip fracture patients has also been compared to the NHFS and POSSUM in prior studies [ 45 , 46 ]. In some, the NHFS performs slightly better and in others POSSUM performs marginally worse, but overall, these indices have a comparable predictive ability when all studies are taken into consideration [ 45 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This seems to indicate that the RCRI has the same level of predictive ability as the CCI. Consequently, the RCRI should also be comparable to the NHFS and POSSUM as they both have an equivalent predictive power to the CCI [ 45 , 46 ]. It might therefore be argued that the RCRI is preferable to all of these indices.…”
Section: Discussionmentioning
confidence: 99%
“…A similar performance for 180-day mortality of the CCI was found by Boddaert et al [ 26 ] (AUC 0.64), whereas Hautamäki found better results (AUC 0.77) for 180-day mortality [ 27 ]. An age-adjusted developed score might be more suitable, but further studies are needed to verify its prediction power [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the literature, the POSSUM, as well as the P-POSSUM, performed poorly in general, being similar to the 30-day mortality findings of Ramanathan et al (AUC 0.62) in particular when compared to the AUC values for POSSUM in general surgery of >0.9 and general orthopedics of >0.85 [ 29 , 30 ]. Burgos et al [ 31 ], Nelson et al [ 28 ] and Karres et al [ 32 ] also evaluated different scoring systems in hip fractures in a frail population, including the CCI and POSSUM. The authors came to different values for the CCI or POSSUM, showing a big range in the results for 30-day mortality, whereas Karres et al [ 32 ] reported an AUC for the CCI of 0.69 and 0.71 for the POSSUM, Burgos et al [ 31 ] had an AUC of 0.64 for the CCI and 0.59 for POSSUM and Nelson et al had an AUC of 0.77 for CCI and 0.76 for POSSUM for 30 day-mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation